Gender Equality for the Education Sasak Muslim Women in Lombok, 1943-1987: Perspective of the Hierarchy of Human Needs - Purnama, Lalu Wahyu Andi; Muhsin, Imam; Hadi, Muhammad Shulhan (Universitas Hamzanwadi, 2026)
Until the early 20th century, Sasak society regarded Muslim women as second class citizens unworthy of receiving education similar to their male counterparts. This perception changed in 1943 when a special educational institution for Muslimah was established. This study aims to explain the life of the Sasak community prior to the establishment of Nahdlatul Banat Diniyah Islamiyah, the development of Islamic education for Sasak women, and the implications of gender equality in education for the advancement of Sasak Muslim women from the perspective of the hierarchy of human needs. Methodologically, this study utilizes a historical approach, incorporating data analysis hierarchy of human needs theory. Results in this paper indicate that the Sasak society, prior to the inception of NBDI, can be categorized into three distinct phases: the initial phase marked by the dominance of animism and dynamism beliefs, the succeeding phase marked the era of Hindu-Buddhist influence, followed by the third phase distinguished by the impact of Islamic influence. The subsequent discussion focuses on the inception and development of education, initially concentrated on males. In 1943, a bright future for women's education found its momentum with the establishment of the first Islamic educational institution dedicated to women. Since that time, considerable advancements have been observed in the presence of Sasak women. Examining hierarchy of human needs, Sasak women after conducted advocacy for gender equality has been changed. This has led to an equitable standing between men and women, ultimately attaining self-actualization as the apex of their hierarchy of needs.